Hubungan Kepatuhan Minum Obat terhadap Keberhasilan Terapi pada Pasien Hipertensi di Puskesmas Prambanan Sleman Bulan Januari – Februari 2020 - Hesti Sumiasih; Trilestari; Widyaningrum Utami (STIKES MUHAMMADIYAH KLATEN, 2020)
Hypertension or high blood pressure can be interpreted as an increase in systolic and diastolic blood pressure of more than 140 mmHg. Hypertension is often referred to as the silent disease. One of the determining factors for the success of therapy in hypertensive patients is adherence to taking antihypertensive drugs. The purpose of this study was to determine the relationship between medication adherence to the success of therapy in hypertensive patients at Prambanan Public Health Center, Sleman. This research is a non-experimental research with analytical survey method and cross sectional design. The study was conducted on 100 respondents who met the inclusion and exclusion criteria. The research was conducted from January to February 2020. The research instrument used was the MMAS-8 questionnaire which had been tested for validity and reliability. The relationship between the level of adherence and the success of therapy was analyzed using the Chi-Square test. Patient adherence rate was 32% high, 44% moderate, and 24% low. Patients who achieved therapeutic success were 57% and did not achieve therapeutic success as much as 43%. Based on the results of statistical analysis using the Chi-Square test, the results showed P = 0.037. This shows that there is a significant relationship between medication adherence to the success of therapy in hypertensive patients at Prambanan Public Health Center, Sleman.